Comprehensive Analysis of Nation Branding: Methodologies, Implications, Indexes, and Future Directions. - Hongquan, Long (UMA Editorial, 2025)
The thesis offers a comprehensive analysis of nation branding, focusing on its methodologies, impacts, and the future of the field. Nation branding is positioned as a key strategy for countries to navigate globalisation, enhance international reputation, attract investment, and stimulate economic growth. The study centres on three major indices—the Anholt-GfK Nation Brands Index (NBI), FutureBrand Country Index (FCI), and Global Soft Power Index—comparing their methods, strengths, and limitations in evaluating national identity and reputation. Using a mixed-methods approach, including bibliometric analysis from Scopus and Web of Science and literature review, the research traces the academic development of the field and its interdisciplinary nature. It provides a comparative study of the three indices: NBI’s public opinion surveys, FCI’s expert-based evaluations, and the Global Soft Power Index’s focus on digital presence and perception. These differences highlight the complexity of capturing a nation’s image through varied metrics. The thesis underscores the importance of inclusive and adaptable branding strategies, urging policymakers to refine practices that truly reflect evolving national identities. It advocates for multidisciplinary collaboration to create transparent and effective branding methods, enhancing international relations and sustainable development. Finally, the research identifies future paths, including the growing role of digital media and the need for new metrics in assessing soft power. It concludes by calling for nation branding approaches that foster authentic, positive images in an increasingly interconnected world.
Texto completo embargado por motivos de confidencialidad. Disponible sólo el resumen.
Keywords: Relaciones internacionales; Relaciones públicas; Nation branding; Country branding; Nation image; Systematic review; Bibliometric analysis